Emotion Classification with DEAP Dataset:Survey [DEAP Veri Seti ile Yapilan Duygu Siniflandirmalari: Inceleme] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Emotions affect our decision making as well as human interactions in our daily lives. Therefore, contributing to commercial activities such as the classification of emotions, neuromarketing and game industry; to be able to communicate with people who cannot express their feelings due to their disability; It has been a popular research topic for many purposes such as being able to determine the accuracy of expressions during the query and creating emotions in humanoid robots. In the researches, it is aimed to increase the classification success by using various methods. Since it is difficult for people to interfere with EEG signals in emotion classification, more realistic determinations can be made. Therefore, the examination of EEG data for emotion classification is an area that needs to be updated and developed. The most popular open source dataset used in emotion classification studies with EEG is the DEAP dataset. In this article, it is aimed to shed light on future studies by examining the classification studies made with DEAP data set. © 2020 IEEE.
Keywords: DEAP; EEG; emotion classification